Claudia Jacobi. Proust dixit ? Réceptions de La Recherche dans l’autofiction de Serge Doubrovsky, Carmen Martín Gaite et Walter Siti. Bonn UP, 2016. - Viviana Pezzullo (Studies in 20th & 21st Century Literature, 2019)
Review of Claudia Jacobi. Proust dixit ? Réceptions de La Recherche dans l’autofiction de Serge Doubrovsky, Carmen Martín Gaite et Walter Siti. Bonn UP, 2016. 299 pp.
Keywords: Proust; autofiction; Claudia Jacobi